Paradigm shift in the regulatory application of safety management systems to offshore facilities. Issue 4 (8th February 2013) - Maher, Steven T.; Long, George D.; Cromartie, Ramine S.; Sutton, Ian S.; Steinhilber, Mark R.
Abstract : The April 2010 Deepwater Horizon tragedy and release from the Macondo Well resulted in a re‐examination of the existing regulatory framework, significant modifications to the structure and function of key regulatory agencies, and the application of new Safety Management System requirements to offshore facilities in United States waters. Late‐2010 witnessed the evolution of both prescriptive and performance‐based regulations designed to address the direct and underlying causes of this tragedy. The objective of this article is to briefly review these new regulatory requirements and illustrate how they are related to the application of other Safety Management Systems, for both offshore and onshore facilities. The common themes, objectives, and overlaps of specific onshore and offshore Safety Management System elements was examined, and tips on how these overlaps can be used to more effectively (and sensibly) implement these programs is discussed. This article also outlined successful Safety Management System programs that are being applied by various state agencies to onshore and offshore coastal facilities, and derived lessons‐learned from these programs that may assist in the implementation of related federal programs. © 2016 American Institute of Chemical Engineers Process Saf Prog 35: 317–329, 2016